Anti-Wolbachia drugs for filariasis. Issue 12 (December 2021) - Johnston, Kelly L.; Hong, W. David; Turner, Joseph D.; O'Neill, Paul M.; Ward, Stephen A.; Taylor, Mark J.
Abstract : The mutualistic association between Wolbachia endosymbionts and their filarial nematode hosts has been exploited as a validated drug target delivering macrofilaricidal outcomes. Limitations of existing antibiotics to scale-up have driven the search for new drugs, which are effective in shorter regimens of 7 days or less. Here, we review the last 14 years of anti- Wolbachia drug discovery by the anti- Wolbachia (A·WOL) consortium, which has screened more than two million compounds, delivering thousands of hit compounds. Refined screening models integrated with robust pharmacokinetic/pharmacodynamic (PK/PD) driven optimisation and selection strategies have delivered the first two drug candidates specifically designed to target Wolbachia. AWZ1066S and ABBV-4083 are currently progressing through clinical trials with the aim of delivering safe and effective macrofilaricides to support the elimination of onchocerciasis and lymphatic filariasis. Highlights: Wolbachia bacterial endosymbionts are a validated drug target for onchocerciasis and lymphatic filariasis delivering macrofilaricidal outcomes. The need for a macrofilaricide is recognised as a critical requirement for onchocerciasis elimination by the World Health Organization (WHO) neglected tropical disease (NTD) roadmap 2021–2030. The anti- Wolbachia (A·WOL) consortium has screened >two million compounds delivering 20 000+ hits and dozens of new chemical series. Two A·WOL clinical candidates – AWZ1066S and ABBV-4083 – are currently progressing through Phase I and Phase II clinical trials.